2021
DOI: 10.3390/microorganisms9061291
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Impacts of Microbiota on Pyropia yezoensis and Surrounding Seawater in Cultivation Farms along Coastal Areas of the Yellow Sea

Abstract: Pyropia yezoensis is the most important commercial edible red algae in China, carrying a variety of resident microbes at its surface. To understand microbiome diversity, community structure, interactions and functions with hosts in this regard, thalli and seawater sampleswere collected from Yantai and Rizhao cultivation farms in the Yellow Sea. The thalli and seawater samples (n = 12) were collected and studied using an Illumina NovaSeq 6000 platform and 16S ribosomal RNA (rRNA) gene sequencing, along with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 121 publications
(117 reference statements)
0
13
0
Order By: Relevance
“…The germplasm preparing process of Neopyropia was easy by cutting thallus into tissues and placing seawater for static culture. Recent research showed that Neopyropia and the surrounding seawater in China were predominately attached by cyanobacteria [16,17]. Our 16S rRNA gene high-throughput sequencing showed that the thallus of Neopyropia (NP1, NP2, NP3) and seawater samples (SW1, SW2, SW3) were enriched with different kinds of cyanobacteria, and seawater had a much higher diversity than N. yezoensis.…”
Section: Leptolyngbya and Nodosilinea Were From Seawater And Neopyropiamentioning
confidence: 72%
See 1 more Smart Citation
“…The germplasm preparing process of Neopyropia was easy by cutting thallus into tissues and placing seawater for static culture. Recent research showed that Neopyropia and the surrounding seawater in China were predominately attached by cyanobacteria [16,17]. Our 16S rRNA gene high-throughput sequencing showed that the thallus of Neopyropia (NP1, NP2, NP3) and seawater samples (SW1, SW2, SW3) were enriched with different kinds of cyanobacteria, and seawater had a much higher diversity than N. yezoensis.…”
Section: Leptolyngbya and Nodosilinea Were From Seawater And Neopyropiamentioning
confidence: 72%
“…In the ultrastructure of Neopyropia, attachment of filamentous cyanobacteria was found, and they were easier to colonize the holdfast of Neopyropia [13]. In addition, the 16S rRNA gene high-throughput sequencing further indicated that the thallus of Neopyropia and surrounding seawater were predominated by cyanobacteria [16,17]. At present, a polyphasic approach combining morphological, ultrastructural, and molecular studies was the most progressive method in the modern taxonomic study of cyanobacteria [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of phytohormone anabolism, the relative abundance of MAGs with IAA synthesis potential exceeded 60% in both groups (RZ vs. ND: 77.58% vs. 61.76%); the relative abundance of MAGs with metabolic ACC potential was higher in the ND group (35.78% vs. 53.05%). Both environment and algae are capable of influencing the community structure of epiphytic microorganisms, so we speculate that the reason for these differences may be the result of a combination of environmental and algal effects ( Yan et al, 2019 ; Wang et al, 2020 ; Ahmed et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…All steps were performed on a clean bench. Metagenomic DNA was extracted using the DNeasy PowerSoil Kit (QIAGEN, Germany), according to the manufacturer’s instructions ( Yan et al, 2019 ; Ahmed et al, 2021 ). The concentration of the extracted DNA was determined using the NanoDrop ND-2000 spectrophotometer (NanoDrop, Wilmington, DE, United States), and the mass was evaluated using a 1% agarose gel.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Wang et al (2020) showed a notable distinction between the microbial communities of seawater with and without N. haitanensis cultivation. Not only did the bacterial biodiversity in the culture zones of Sargassum fusiforme , Neopyropia yezoensis , Sargassum incisifolium , and Phyllospora comosa show significant differences, but it was also greatly influenced by abiotic factors ( Selvarajan et al, 2019 ; Ahmed and Khurshid, 2021 ; Zhang et al, 2021 ; Wood et al, 2022 ). These results indicated that seaweed cultivation has a strong capacity to shape the bacterial community of seawater.…”
Section: Introductionmentioning
confidence: 99%